Exploring pest mitigation research and management associated with the global wood packaging supply chain: What and where are the weak links? - Greenwood, Leigh F.; Coyle, David R.; Guerrero, María E.; Hernández, Gustavo; MacQuarrie, Chris J. K.; Trejo, Oscar; Noseworthy, Meghan K. (Biological invasions, 2023)
Global trade continues to increase in volume, speed, geographic scope, diversity of goods, and types of conveyances, which has resulted in a parallel increase in both quantity and types of pathways available for plant pests to move via trade. Wood packaging material (WPM) such as dunnage, pallets, crates, and spools, is an integral part of the global supply chain due to its function in containing, protecting, and supporting the movement of traded commodities. The use of untreated solid wood for WPM introduces the risk of wood boring and wood-infesting organisms into the supply chain, while the handling and storage conditions of treated WPM presents risk of post-treatment contamination by surface-adhering or sheltering pests. The wood-boring and -infesting pest risks intrinsic to the solid wood packaging pathway were addressed in the 2002 adoption and 2009 revision of ISPM 15, which was first implemented in 2005–2006 in North America. Although this global initiative has been widely implemented, some pest movement still occurs due to a combination of factors including; fraud, use of untreated material, insufficient- or incomplete- treatment, and post-treatment contamination. Here we examine the forest-to-recycling production and utilization chain for wood packaging material with respect to the dynamics of wood-infesting and contaminating pest incidence within the environments of the international supply chain and provide opportunities for improvements in pest risk reduction. We detail and discuss each step of the chain, the current systems in place, and regulatory environments. We discuss knowledge gaps, research opportunities and recommendations for improvements for each step. This big picture perspective allows for a full system review of where new or improved pest risk management strategies could be explored to improve our current knowledge and regulations.